Suntik Hormon Meningkatkan 20lbs Masa Otot? Natural vs Steroid - Rizki Oktario (Journal of Information Systems and Management (JISMA), 2023)
themselves are derivative products of the male sex hormone, namely Testosterone. Testosterone is a male sex hormone that affects hair quality, bone density, voice, mood, sexual level, protein absorption for muscle formation, and of course, good protein absorption can form more muscle mass. This study report uses a descriptive qualitative method by taking notes because of what was obtained by listening to the oral narrative from Jeff Nippard's YouTube channel entitled "How Much Muscle Do Steroids Add?" which was explained by Jeff Nippard. The video explains from a scientific perspective how much muscle mass can be built if you use steroids or do not use (natural) steroids. The natural athletes we will use as examples are Alex Leonidas (AlphaDestiny), and Geoffrey Verity Schofield as examples of athletes in the Pre-Steroid era, and we will look at IFBB Classic Physique champion Mr. Olympia Chris Bumstread as an example of an Athlete using Steroids. Of course, we will discuss the side effects of using steroids and determine whether or not we should use anabolic steroids.